Forward converters for dual voltage switched reluctance motor drives. - Barnes, M. (IEEE Transactions on power electronics)
A new circuit is presented which allows a switched reluctance motor to operate from AC mains or a low voltage battery supply. In addition the AC mains can be used to charge the battery. The switched reluctance motor is used as the voltage-changing transformer, potentially reducing the cost of the system. The operation of the drive is explained, and results of an experimental prototype are presented